Nurture vs. nurture: Endogenous parental and peer effects and the transmission of culture - Daniel Vaughan (Banco de México, 2013)
I propose a model of cultural transmission where children interact strategically with each other with the only desire to fit in, and parents purposefully socialize their children to their own culture. In the empirical section I estimate parental and peer effects using US teenager data on religious attitudes and alcohol consumption from the Add Health study. I find that, controlling for individual and school observables, children attitudes are a weighted average of their parents' and peers' attitudes, with the latter generally dominating. I then show that these are stable in time with now signs of fading away in the transition from adolescence to adulthood. Finally, the comparative statics allow me to separate endogenous from exogenous parental effects.
Keywords: D19; J13; J15; 330; cultural transmission; endogenous preferences; add health study; preference for conformity; endogenous socialization